The role of agricultural cooperatives in the development and promotion of rural tourism: A case study of Azanja, Serbia - Dejanović Aleksandar; Lukić-Nikolić Jelena (Marketing (Beograd. 1991))
The aim of this paper is to examine and analyze the role of agricultural cooperatives in the development and promotion of rural tourism. The research was conducted in Azanja, Serbia, utilizing a mixed-method research with a questionnaire technique and a case study method during March and April 2024. The key findings indicate that improving conditions for rural tourism development requires effective networking among all stakeholders and coordinated promotional activities. Establishing partnerships based on shared interests is essential for rural tourism development. In this context, the agricultural cooperative Azanja should assume several important roles: initiator, educator, coordinator, logistics organizer, tourism animator, promoter, consultant, and supervisor. By taking on these responsibilities, Azanja can effectively support and stimulate rural tourism development. Furthermore, the agricultural cooperative Azanja has the ability to develop effective promotional strategies to increase the area's visibility on the tourist map.